HUBUNGAN PERBURUHAN ERA DESENTRALISASI DI KECAMATAN MANDAU KABUPATEN BENGKALIS TAHUN 2013-2015 - Panjaitan, Firza Novita; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the interests of workers in the District of Mandau in 2013-2015, a means of fighting for the interests of workers in the District of Mandau in 2013-2015, as well as Human Resources (HR) in Bengkalis Regency in 2013-2015. As for the background in this research is the problem of fulfillment of the normative rights of uncooperative workers in Mandau Sub-district, while the oil and gas sector becomes a source of income that contributes greatly to the increase of local revenue (PAD) in the area. But it is unfortunate that it is not followed by the increase of welfare for the community, especially for the contract workers who work in the company contractors partners PT. Chevron Pacific Indonesia (PT CPI). The research method used in this research is descriptive qualitative method, where in this research, the researcher tried to explain about the problems that happened between 8 (eight) PT. CPI and workers working in the company. Then the data collection techniques in this study using in-depth interview techniques and documentation of data collection and facts related to research problems. Further data obtained from the research location will be processed and analyzed further by way of describing the facts that have been found from the location of the study. From the results of interviews to informants and based on the data and information obtained by researchers when conducting research, it can be concluded that the demand for the settlement of problems related to the non-fulfillment of the normative rights of the workers is the interests fought by workers in the District of Mandau Bengkalis Regency on year 2013-2015. Then in the struggle for these interests, there are 4 (four) means employed by the workers in solving the problem, namely Labor Union, Labor Law Regulation, Bipartite Cooperation Institution, and Industrial Relations Dispute Settlement Institution. In addition, to improve the quality of Human Resources (HR) in Mandau District, especially in terms of potential management of the oil and gas sector, the local government of Bengkalis Regency builds a Vocational High School (SMK) based on Petroleum, so as to improve the competitiveness of the community, especially the younger generation in Mandau Sub- Regency of Bengkalis.Keywords: Labour Relations, Labour Interest, Fulfillment of Normative Rights, Mandau Sub-district.